REPRESENTASI GAY DALAM FILM MOONLIGHT - Elisa Gunawati; Feri Ferdinan Alamsyah; Roni Jayawinangun (UNIVERSITAS PAKUAN, 2020)
Gay or homosexuality is a variation of developed sexual orientation in society. The purpose of this research is to know the gay representation in Moonlight film and to know semiotic analysis of Charles Sanders Peirce in Moonlight film. Research design and research method used in this thesis is qualitative research method of Semiotics Charles Sanders Peirce and Queer Theory. The analysis of each scene has been selected as many as six scenes showing gay signs and then analyzing using Peirce model that is relation of Sign / Interpretant, Object, and Interpretant which each consist of trichotomy based on the sign that is qualisign, sinsign, and legisign, based on the object ie icon, index, and symbol, and based on interpretantnya rheme, dicisign, and argument. After observing and analyzing the scene / scene in the movie